Performing touch and smell - Toporišič, Tomaž (Amfiteater (Ljubljana), 2021)
The paper discusses the liminal nature of the sensorial languages in contemporary performing arts. Its starting point will be the following chain of thoughts: during artistic events, a performative action reshaping the performers and the audience takes place, along with the interchange of the roles between the “stage” and “auditorium”, either in the sense of Augusto Boal’s spect-actor or the destruction of the fourth wall and the specific “autopoietic feedback loop” (Erika Fischer-Lichte) between both parties involved. We aim to rethink and re-examine the role of the sensorial language as one of the rarely used yet highly efficient tools of the performative revolutions of the 20th and 21st centuries. These revolutions started with the Futurists, continued with the tactile and sensorial performances and politics of Marina Abramović and Yoko Ono, and culminated with Enrique Vargas and his sensorial theatre in different stages from New York’s La Mama radical 1960s productions to his 1990s new sensorial theatre language of his Teatro de los Sentidos. We will try to answer the following questions: How can and how do we touch and smell … in performative actions? Which kind of liminalities does the act of sensorial produce in a contemporary performance?
Keywords: Enrique Vargas; immersive theatre; liminality; liminalnost; performance art; performans; potopitveno gledališče; sensorial theatre; senzorično gledališče